Integrating technological advancements in Behavioral Interventions to Promote health: Unprecedented opportunities for Behavior analysts - Allison N. Kurti (Revista Mexicana de Análisis de la Conducta, 2014)
The use of mobile devices is growing worldwide in both industrialized and develop ing nations. Alongside the worldwide penetration of webenabled devices, the leading causes of morbidity and mortality are increasingly modifiable lifestyle factors (e.g., improving one’s diet and exercising more). Behavior analysts have the opportunity to promote health by combining effective behavioral methods with technological ad vancements. The objectives of this paper are (1) to highlight the public health gains that may be achieved by integrating technology with a behavior analytic approach to developing interventions, and (2) to review some of the currently, underexamined issues related to merging technology and behavior analysis (enhancing sustainability, obtaining frequent measures of behavior, conducting component analyses, evaluating costeffectiveness, incorporating behavior analysis in the creation of consumerbased applications, and reducing health disparities). Thorough consideration of these issues may inspire the development, implementation, and dissemination of innovative, effi cacious interventions that substantially improve global public health.